Exploring the Education of Nursing and Midwifery Preceptors and Their Perceived Self-Efficacy in Role Performance: A Cross-Sectional Evaluation - Hardie, Philip (My University, 2025)
Background: Preceptorship is a vital component of nursing and midwifery education, facilitating skill development, confidence and professional socialisation of students and newly qualified nurses and midwives. There is currently a gap in the available literature on the education preceptors in the Republic of Ireland receive. Aim: To explore the training and education received by nurses and midwives as preceptors in the Republic of Ireland and to assess their self-efficacy in fulfilling key preceptorship roles and responsibilities. Methods: A descriptive, cross-sectional survey design was employed, utilising a structured, anonymous questionnaire distributed nationally to registered nurses and midwives acting as preceptors. Results: Preceptors reported considerable variability in training, with some participants indicating no formal preparation for the role. Most training was lecture-based. Preceptors expressed high confidence in interpersonal and leadership skills but lower confidence in managing underperforming students. Over half of the participants felt adequately prepared, indicating potential for enhanced education and support within the curriculum. Conclusions: A standardised, evidence-based preceptorship educational programme incorporating diverse, experiential teaching methods is needed to better prepare nursing and midwifery preceptors in Ireland.
PUBLISHED
Keywords: Preceptorship; Preceptorship Education & Training; Role and Responsibilities Self-efficacy; Digital Engagement